Indolicidin – Antibacterial activity against bacterial pathogens isolated from ocular infections - Nambirajan, G; Annamalai, B; Shobana, C S; Panneer Selvam, K (Recent Research in Science and Technology, 2015)
Indolicidin is a novel/ promising antimicrobial peptide (a 13 amino acid cationic antimicrobial residue present in the form of cytoplasmic granules of bovine neutrophils) and observed with a broad spectrum of antimicrobial activity against bacteria, fungi, protozoa & even viruses. In the present study, Escherichia coli was transformed with pET 21a+ plasmid carrying indolicidin gene and was expressed. The crude extracts of indolicidin samples induced with varying IPTG concentrations (5mM and 20 mM/ ml of the medium) in Min A medium were checked for antibacterial activities against clinically important ocular bacterial pathogens such as E. coli, Klebsiella sp,, Pseudomonas sp., Acenitobacter sp., Staphylococcus aureus, coagulase negative Staphylococcus aureus, Streptococcus viridans, S. pneumoniae and S. pyogens and its activity was evaluated.